Problems of Modernization of Information Security of the Republic of Armenia - Gzoghyan, Mariam (YSU Journal of International Affairs, 2024)
In contemporary international relations, states place significant emphasis on the matters of modernization and the upkeep of information security mechanisms. It is important to highlight that with the increasing role and volume of information, the threats to information security have correspondingly grown. Consequently, safeguarding information has emerged as a foremost focal point within the domestic and foreign policies of numerous states. Analyzing various scientific works, I consider it necessary to emphasize that in the past, security was primarily associated with military aspects in both scientific and political contexts, today, there is a growing focus on the non-military dimensions of security. As a result, states and international organizations are now tasked with ensuring collective security across various domains, including politics, economics, society, ecology, and the military. Moreover, according to the nature of their regime, countries solve the problem in different ways. Some close the information field, banning even the use of social networks, others are looking for more liberal methods (Mkrtchyan H., 2018, p. 55). Advancements in information technology and telecommunications have become an important tool for promoting their own interests and goals in international exchanges, so states spare no effort in establishing professional ’information armies’ and secure information infrastructures. Recent global experience demonstrates that the influence of information flows can be a powerful weapon for states conducting actions against their adversaries. States lacking the capacity to counter this weapon may find themselves at a disadvantage. Starting from a political science perspective, it emphasizes the necessity of the private sector and state institutions to collaborate in countering various threats in the field of information security.